2001
DOI: 10.1054/bjoc.2000.1675
|View full text |Cite
|
Sign up to set email alerts
|

Frequent k- ras -2 mutations and p16INK4Amethylation in hepatocellular carcinomas in workers exposed to vinyl chloride

Abstract: Summary Vinyl chloride (VC) is a know animal and human carcinogen associated with liver angiosarcomas (LAS) and hepatocellular carcinomas (HCC). In VC-associated LAS mutations of the K-ras-2 gene have been reported; however, no data about the prevalence of such mutations in VC associated HCCs are available. Recent data indicate K-ras-2 mutations induce P16 methylation accompanied by inactivation of the p16 gene. The presence of K-ras-2 mutations was analysed in tissue from 18 patients with VC associated HCCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…induce specific gene mutations in the liver [105][106][107][108][109][110][111][112][113][114][115][116][117] . Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…induce specific gene mutations in the liver [105][106][107][108][109][110][111][112][113][114][115][116][117] . Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…Recently, the presence of KRAS2 mutations was observed in 33% of 18 vinyl chloride-associated HCCs and three mutations were found in adjacent nonneoplastic liver tissue (Weihrauch et al, 2001). The KRAS mutations observed were probably caused by chloroethylene oxide, a carcinogenic metabolite of vinyl chloride.…”
Section: Genetic Alterations and Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Loss of heterozygosity at the short arm of chromosome 9, in the region of p16 INK4 , was found in about 20% of HCC cases (Boige et al, 1997;Nagai et al, 1997;Laurent-Puig et al, 2001). Methylation of the p16 INK4 promoter leading to the absence of protein expression was found in 30-70% of the tumors (Liew et al, 1999;Matsuda et al, 1999;Jin et al, 2000;Weihrauch et al, 2001). Somatic inactivating mutations and homozygous deletions of the gene are rarely observed in HCC (Biden et al, 1997;Jin et al, 2000).…”
Section: )mentioning
confidence: 99%
“…This is similar to the findings of previous studies, which reported that the K-Ras mutation is an uncommon or even rare event in HCC. This is in contrast to the frequent presence of K-Ras mutations in chemical models of HCC in animals (1,(19)(20)(21)(22)(23)(24). Considering the small sample size of the previous and present studies, the true prevalence of K-Ras mutations in HCC has yet to be determined.…”
Section: Discussionmentioning
confidence: 60%